STUDY OF QUASI–PERIODIC VARIATIONS IN DRAG OF ARTIFICIAL SATELLITE DURING 23–24 SOLAR CYCLES - Komendant, V. H.; Ryabov, M. I.; Sukharev, A. L. (Одеські астрономічні публікації, 2016)
Apply of the method of time-frequency analysis allows to reveal the detailed structure of the manifestations of the influence of the state space weather on the upper atmosphere of the Earth. Sensitive indicators of such changes are low-orbit satellites. The dynamics of drag of nineteen low–orbit satellites was viewed. The study period includes phases of declining and a long minimum of 23rd solar cycle, phases of rise and maximum of 24th solar cycle. In dynamic of inhibition of all the analyzed satellite pronounced regular inhibition effects with extended periods of 2 – 6 years and short-period effects with periods less than one year. In the satellites: 00063, 00165, 25064, 00932 and 00746 – detected periods with trend from 25 – 28 days to 1 – 1.7 months.